CODON OPTIMIZATION OF SERRATIA MARCESCENS CHIA AND ITS EXPRESSION IN TOBACCO - M. A. Pasha; A. Belgaumwala; R. Kumar; P. U. Krishnaraj; M. S. Kuruvinashetti (Journal of Animal and Plant Sciences, 2015)
Most plant diseases are caused by fungal pathogens, which contain chitin as their major cell wall component, except Oomycetes. Chitinases cleave between C1 and C4 of two consecutive N-acetylglucosamine of chitin. Among bacterial chitinases, Serratia marcescens chitinases have been studied well. In order to develop intrinsic resistance, genes from various sources have been cloned and expressed in plants but in most cases, the transgene failed to produce desired quantity of foreign protein in the heterologous system. Codon optimization is a general approach for improving expression of gene in any heterologous system. Full length chiA (1692 bp) from S. marcescens 141 (sm141chiA) was considered for removal of regulatory signals (partial optimized- sm141chiApm) and replacement of rare codons with preferred codons by tobacco (fully optimized- sm141chiAfm). Of 1692 bp, 22 and 432 nucleotides were altered to get partial and fully optimized genes, respectively. The synthesized gene was sub-cloned in plant expression vectors and transferred to tobacco. The plants containing sm141chiApm produced 1.82 fold more reducing equivalents whereas plants containing sm141chiAfm produced 4.39 fold more reducing equivalents compared to the plants containing sm141chiA. Optimization of bacterial codons to suit the plant codon dictionary improved the expression level of chitinase in tobacco by 2.57 fold. For high level expression of transegene in heterologous system, the codon frequency of transgene should be similar to the codons preferred by high level expressing genes in host.
Keywords: Chitinase; Serratiamarcescens; codon optimization; transgenic tobacco; regulatory sequences